Guidelines for the use of advanced numerical analysis - Potts, David, 1952- (Thomas Telford, 2002)
It is not easy for engineers to gain all the skills necessary to perform numerical analysis. This book is an authoritative guide that explains in detail the potential restrictions and pitfalls and so help engineers undertake advanced numerical analysis.